Protists have divergent effects on bacterial diversity along a productivity gradient. - Bell, T; Bonsall, M; Buckling, A; Whiteley, A; Goodall, T; Griffiths, R (2010)
Productivity and predation are thought to be crucial drivers of bacterial diversity. We tested how the productivity-diversity of a natural bacterial community is modified by the presence of protist predators with different feeding preferences. In the absence of predators, there was a unimodal relationship between bacterial diversity and productivity. We found that three protist species (Bodo, Spumella and Cyclidium) had widely divergent effects on bacterial diversity across the productivity gradient. Bodo and Cyclidium had little effect on the shape of the productivity-diversity gradient, while Spumella flattened the relationship. We explain these results in terms of the feeding preferences of these predators.